Satisfaction with utilisation of national health insurance among selected community people of Bharatpur, Nepal - Neupane, Sadikshya; Ghimire, Srijana (Journal of Chitwan Medical College, 2025)
Introduction: Health insurance program plays an important role in health care delivery system. This study aimed to find out satisfaction with utilisation of national health insurance. Method: A descriptive cross-sectional study was conducted among community people of Bharatpur-11 from 15 Aug 2024 to 14 Sep 2024. Community people enrolled in national health insurance program and who received at least one service were selected as per calculated sample size by using non-probability purposive sampling technique. Ethical approval was obtained. Data were collected using face-to-face structured interview method. Data were analysed using descriptive statistics (frequency, percentage, central tendency, measures of dispersion). Result: Out of 119 respondents, 56(47.10%) were satisfied towards utilisation of national health insurance. Among different subscales, two-thirds (76.66%) were satisfied on hospital facility followed by registration (75.0%). Conclusion: In this study, fewer than half respondents were satisfied regarding utilisation of national health insurance. Supervision and improvement in health care services are necessary.